The relationship between using online social networking and psychological well-being - Wong, Pui Yee (2016)
SNSs have become ubiquitous across the globe. Although many researchers shed the light on SNSs use, little research investigates the relationship between SNSs use and the psychological impacts on users. This review examines the relationship between using online social networking (OSN) and psychological well-being (PWB) by means of subjective well-being (SWB), loneliness and depression. Mutual self-disclosure and authenticity on SNSs provides opportunities for social support seeking and provision. This, in turn, increases SWB. In contrast, SNSs use can be harmful if individuals get addicted to the virtual world. Correspondingly, studies indicate that engaging in SNSs activities is able to alleviate loneliness provided that individuals use SNSs actively for a social purpose. This is because such usage can heighten users’ feelings of social connectedness. Research interestingly shows that lonely individuals are likely to increase their SNSs use for social compensation. Unfortunately, this is going to get them to problematic SNSs use but not helping them to relief feelings of loneliness. Besides, a contradictory result is found in depression. Evidence indicates that SNSs use could lead to the development of depressive symptoms. This is because SNSs have placed individuals at great risk for negative social comparisons. Researchers also acknowledge that depressed individuals incline to use SNSs to satisfy their social needs. However, it shows that SNSs have become an additional platform for them to display their problematic social skills. In sum, the present study contributes to the field of psychology, proving that OSN has significant impacts on psychological well-being.